Evolution Mechanism of Thickly Sticky Loose Layered Arch Structure and Prediction Method of Initial Ground Fissure Caused by Underground Coal Mining - Yang Yingming; Li Quansheng; Liu Shiliang; Zhang Kai; Zhao Yongqiang; Zhang Guojun; Zhang Weilong; Liu Gang (Geofluids)
In view of the problem of taking the loose layer as the uniform cloth load while ignoring thickly sticky loose layered arch (TSLLA) of the traditional mining rock overburden structure analysis, combined with the geological conditions of shallow buried thickly sticky loose layer in Shendong mining area, the mechanical model of the mining TSLLA bearing structure is established, the variation law of arch height under different loose layers is analyzed, and the formation conditions of TSLLA are given. The first theory deduced the dynamic evolution mechanism of TSLLA structure advancing. The dynamic evolution of TSLLA structure in 22207 coalface is simulated. The formula for the limit height of TSLLA is derived. A classification method of mining loose layer structure is proposed. The loose layer structure type is divided into load type, arch beam type damage type, and limit arch height type. On this basis, the mechanical model of “arch beam” is constructed. The influence mechanism of the TSLLA on the surface cracks is revealed. The methods and calculation steps for initial surface cracks are presented. The results are verified by the measured data of surface subsidence of the typical thickly sticky layer in Shendong mining area.